(untitled) (Patrimônio e Memória, 2011)
This article investigates the history, social memory and heritage of Engenheiro Correa, a rural district in Ouro Preto city, in the State of Minas Gerais. Like most of the settlements arranged around the city, this location emerged in the late 17th century or the beginning of the following century; a result of the demographic occupation which resulted in the State of Minas Gerais. We evaluate the insertion of this district into the historical process of Minas; the peculiarities of its local development, and its existing heritage and memorial legacy.